Induction of early Purkinje cell dendritic differentiation by thyroid hormone requires RORα - Boukhtouche, Fatiha (BioMed Central, 2010)
BACKGROUND: The active form (T(3)) of thyroid hormone (TH) controls critical aspects of cerebellar development, such as migration of postmitotic neurons and terminal dendritic differentiation of Purkinje cells. The effects of T(3 )on early dendritic differentiation are poorly understood. RESULTS: In this study, we have analyzed the influence of T(3 )on the progression of the early steps of Purkinje cell dendritic differentiation in postnatal day 0 organotypic cerebellar cultures. These steps include, successively, regression of immature neuritic processes, a stellate cell stage, and the extension of several long and mature perisomatic protrusions before the growth of the ultimate dendritic tree. We also studied the involvement of RORα, a nuclear receptor controlling early Purkinje cell dendritic differentiation. We show that T(3 )treatment leads to an accelerated progression of the early steps of dendritic differentiation in culture, together with an increased expression of RORα (mRNA and protein) in both Purkinje cells and interneurons. Finally, we show that T(3 )failed to promote early dendritic differentiation in staggerer RORα-deficient Purkinje cells. CONCLUSIONS: Our results demonstrate that T(3 )action on the early Purkinje cell dendritic differentiation process is mediated by RORα.